Hwanglyunhaedok Pharmacopuncture versus Saline Pharmacopuncture on Chronic Nonbacterial Prostatitis/Chronic Pelvic Pain Syndrome - Kee Moon Seong; Geurin Jang; Dong Woong Kim; Sungchul Kim; Bong Keun Song (Medical Association of Pharmacopuncture Institute, 2017)
Purpose: Chronic nonbacterial prostatitis (CP)/chronic pelvic pain syndrome (CPPS) is known not to have a successful therapy as yet. More recently, acupuncture, some herbal compounds, and trigger point injection have been reported to be beneficial. Pharmacopuncture is an herbal acupuncture having these benefits. The aim of this study was to compare the effect of HP (Hwanglyunhaedok Pharmacopuncture) versus normal saline injection (Saline Pharmacopuncture, SP) on CP/CPPS. Methods: A retrospective follow up study of 63 patients who were diagnosed with CP/CPPS was performed. All patients were treated with electroacupuncture and injected with either 1 ml of HP or SP at CV1 as a standard treatment for 4 weeks. Thus, the patients were classified in two groups: HP (n = 32) and SP group (n = 31). Treatment was applied twice a week every third day for 4 weeks. After 4 weeks, the effect of pharmacopunture in both groups was compared using NIH-CPSI (National Institutes of Health-Chronic Prostatitis Symptom Index) and IPSS (International Prostate Symptom Score) before and after treatment. Results: After treatment, the total NIH-CPSI scores were significantly reduced in both groups (p < 0.01). Pain domain scores in both groups showed significant decrease (p < 0.01). In HP group, urination (p < 0.05) and quality of life (p < 0.01) scores reduced significantly. In SP group, impact score showed significant decrease (p < 0.05). However, impact score in HP group and urination and quality of life scores in SP group didn't show any significance. IPSS score was reduced significantly after treatment in both groups (p < 0.05). Conclusions: These results suggest that pharmacopuncture and electroacupuncture treatment were effective on CP/CPPS. HP and SP didn't show any significant difference. However, it was also confirmed that HP is more favorable than SP to improve the symptoms of CP/CPPS.